At the cross-point of connexins, calcium, and ATP: blocking hemichannels inhibits vasoconstriction of rat small mesenteric arteries. Issue 2 (27th September 2016) - Bol, Mélissa; Wang, Nan; De Bock, Marijke; Wacquier, Benjamin; Decrock, Elke; Gadicherla, Ashish; Decaluwé, Kelly; Vanheel, Bert; van Rijen, Harold Victor Maria; Krysko, Dmitri Vadim; Bultynck, Geert; Dupont, Geneviève; et al.
Abstract : Aims: Connexins form gap-junctions (GJs) that directly connect cells, thereby coordinating vascular cell function and controlling vessel diameter and blood flow. GJs are composed of two hemichannels contributed by each of the connecting cells. Hemichannels also exist as non-junctional channels that, when open, lead to the entry/loss of ions and the escape of ATP. Here we investigated cross-talk between hemichannels and Ca 2+ /purinergic signalling in controlling blood vessel contraction. We hypothesized that hemichannel Ca 2+  entry and ATP release contributes to smooth muscle cell (SMC) Ca 2+  dynamics, thereby influencing vessel contractility. We applied several peptide modulators of hemichannel function and inhibitors of Ca 2+  and ATP signalling to investigate their influence on SMC Ca 2+  dynamics and vessel contractility. Methods and results: Confocal Ca 2+  imaging studies on small mesenteric arteries (SMAs) from rat demonstrated that norepinephrine-induced SMC Ca 2+  oscillations were inhibited by blocking IP3 receptors with xestospongin-C and by interfering with hemichannel function, most notably by the specific Cx43 hemichannel blocking peptide TAT-L2 and by TAT-CT9 that promotes Cx43 hemichannel opening. Evidence for hemichannel involvement in SMC function was supported by the fact that TAT-CT9 significantly increased SMC resting cytoplasmic Ca 2+  concentration, indicating it facilitated Ca 2+  entry, and by the observation that norepinephrine-triggered vessel ATP release was blocked by TAT-L2. Myograph tension measurements on isolated SMAs showed significant inhibition of norepinephrine-triggered contractility by the ATP receptor antagonist suramin, but the strongest effect was observed with TAT-L2 that gave ∼80% inhibition at 37 °C. TAT-L2 inhibition of vessel contraction was significantly reduced in conditional Cx43 knockout animals, indicating the effect was Cx43 hemichannel-dependent. Computational modelling suggested these results could be explained by the opening of a single hemichannel per SMC. Conclusions: These results indicate that Cx43 hemichannels contribute to SMC Ca 2+  dynamics and contractility, by facilitating Ca 2+  entry, ATP release, and purinergic signalling.